Temporal Aspects of Memory: A Comparison of Memory Performance, Processing Speed and Time Estimation Between Young and Older Adults - Ebaid, Deena; Crewther, Sheila G. (Frontiers in Aging Neuroscience, 2018)
Working memory (WM) efficiency is commonly reported to decline with age when assessed with classical WM measures such as the backwards digit span and N-back tasks. However, some debate still exists regarding which aspects of working memory are most susceptible to the aging process and which may remain intact. Additionally, time estimation, though a complex psychological dimension, is particularly neglected in the traditional study of working memory and is often studied in relative isolation. Currently, there is little research on WM from the viewpoint of retrospective temporal estimation, and whether the ability to accurately estimate time retrospectively, is correlated with performance on traditional measures of WM and processing speed in healthy populations. Thus, we chose to investigate performance of comparably educated young and older adult groups on both classical WM tasks including digit span, N-back, and WAIS-based measures of processing speed (i.e., Symbol Search [SS] and Coding [Cod]) and a temporal measure of WM with a focus on retrospective time estimation. Our sample included 66 university students (58 F, 8 M) between the ages of 18 – 29, and 33 university-educated healthy older adults (25 F, 8 M) between the ages of 60 – 81. Results indicated that older adults performed significantly worse on auditory and visual digit span working memory tasks as well as on both the SS and Cod, though equally well on the untimed N-back task. Results also showed that retrospective time estimation was not significantly different between young and older adults, with both groups substantially underestimating task duration. Retrospective time estimation was not significantly correlated to any WM or processing speed measure, providing grounds for future research into the specific cognitive domains underlying the subjective estimation of a temporal interval.